Preventive Supplementation of Omega-3 Reduces Pain and Pro-inflammatory Cytokines in a Mouse Model of Complex Regional Pain Syndrome Type I - de Oliveira Galassi, Taynah; Fernandes, Paula Franson; Salgado, Afonso Shiguemi Inoue; Cidral-Filho, Francisco José; Piovezan, Anna Paula; Lüdtke, Daniela Dero; Mack, Josiel Mileno; Weber, Kenneth A.; Reed, William R.; Bobinski, Franciane; Martins, Daniel F. (Frontiers in Integrative Neuroscience, 2022)
Complex regional pain syndrome type I (CRPS-I) is a condition that responds poorly to treatments. The role of omega-3 fatty acids in the treatment of inflammatory disorders is well described in the literature; however, few studies have evaluated its therapeutic benefits in different types of pain. We evaluated the potential antihyperalgesic and anti-inflammatory effects of preventive omega-3 supplementation in an animal model of CRPS-I. In experiment 1, Swiss female mice were supplemented for 30 days with omega-3 before the induction of the CRPS-I model and 14 days after. Mechanical hyperalgesia was evaluated at baseline and from the 4th to the 14th day after CPRS-I induction along with open field locomotor activity after 30 days of supplementation. In experiment 2, Swiss female mice were supplemented for 30 days with omega-3 and then subjected to the CRPS-I model. Twenty-four hours later the animals were euthanized, and tissue samples of the spinal cord and right posterior paw muscle were taken to measure pro-inflammatory cytokine TNF and IL-1β concentrations. Omega-3 supplementation produced antihyperalgesic and anti-inflammatory effects, as well as reducing pro-inflammatory cytokine concentrations, without altering the animals’ locomotion. No open field locomotor changes were found. The 30-day supplementation at the tested dose was effective in the CRPS-I model.